Federal Financial Incentives to Induce Early Experience Producing Unconventional Liquid Fuels - Camm, Frank (RAND Corporation, 2008)
The government, as a principal, may seek to induce a private investor, as anagent, to build and operate an unconventional-oil production plant topromote early production experience with such plants. Facing significantuncertainty about the future, it also wants to limit the cost to the publicof doing this. This report offers an analytic way to design and assesspackages of policy instruments that the government can use to achieve itsgoal.